2016
DOI: 10.1210/jc.2016-2547
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal Skinfold Thickness: A Novel Parameter for Assessment of Body Composition in Childhood Craniopharyngioma

Abstract: Context:Hypothalamic obesity, cardiovascular disease (CVD), and relapse/progression have a major impact on prognosis in childhood-onset craniopharyngioma (CP). We analyzed nuchal skinfold thickness (NST) on magnetic resonance imaging performed for follow-up monitoring as a novel parameter for body composition (BC) and CVD in CP.Objective:The objective of the study was to identify the association of NST with body mass index (BMI), waist to height ratio (WHtR), functional capacity, and blood pressure (BP) in CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…There is scarce literature on reduced fetal nuchal fold thickness, but a recent study in adults found that nuchal fold thickness was positively correlated with body mass index. 53 We hypothesize that the reduced nuchal fold thickness in SGA is likely due to reduced nuchal adipose tissue, which would be a logical consequence of the reduced growth rates.…”
Section: Discussionmentioning
confidence: 95%
“…There is scarce literature on reduced fetal nuchal fold thickness, but a recent study in adults found that nuchal fold thickness was positively correlated with body mass index. 53 We hypothesize that the reduced nuchal fold thickness in SGA is likely due to reduced nuchal adipose tissue, which would be a logical consequence of the reduced growth rates.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study 25 , analyzing NST on cranial MRIs of craniopharyngioma patients performed during follow-up monitoring, we reported on NST as a new parameter for body composition assessment. We observed that NST was associated with other parameters of body composition such as body mass index, caliper-measured skinfold thickness, and waist-to-height ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of free fatty acid are mainly determined by the upper-body subcutaneous fat compartment, indicating that this compartment plays an important role as speci c risk factor for cardiovascular disease 20 . We could previously show that nuchal skinfold thickness (NST) -as assessed in MRI of craniopharyngioma patients -serves as a predictor of metabolic risk above and beyond waist circumference and body mass index in craniopharyngioma patients [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study ( 27 ), analyzing NST on cranial MRIs of craniopharyngioma patients performed during follow-up monitoring, we reported on NST as a new parameter for body composition assessment. We observed that NST was associated with other parameters of body composition such as BMI, caliper-measured skinfold thickness, and waist-to-height ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of free fatty acid are mainly determined by the upper-body subcutaneous fat compartment, indicating that this compartment plays an important role as specific risk factor for cardiovascular disease ( 22 ). We could previously show that nuchal skinfold thickness (NST) – as assessed in MRI of craniopharyngioma patients – serves as a predictor of metabolic risk above and beyond waist circumference and BMI in craniopharyngioma patients ( 23 27 ).…”
Section: Introductionmentioning
confidence: 99%